Platforms for Cross-Sector Social Partnerships: Prospective Sensemaking Devices for Social Benefit - Selsky, John W. (Journal of business ethics, 2010)
Cross-sector social partnerships (CSSPs) can produce benefits at individual, organizational, sectoral and societal levels. In this article, we argue that the distribution of benefits depends in part on the cognitive frames held by partnership participants. Based on Selsky and Parker’s (J Manage 31(6):849–873, 2005) review of CSSPs, we identify three analytic “platforms” for social partnerships – the resource-dependence platform, the social-issue platform, and the societal-sector platform. We situate platforms as prospective sensemaking devices that help project managers make sense of partnerships by calling attention to certain desired features or downplaying other features. We describe the three platforms and contrast them on factors that influence social benefit, including orientation, learning, and power. We provide illustrations of each platform and demonstrate how the choice of platform is consequential for practice, such as how a partnership project gets started, evolves and produces social benefits.